ANALISIS RAB STRUKTUR BETON GEDUNG TIGA LANTAI MENGGUNAKAN METODE AUTODESK REVIT DAN ANALITIS - Yoga Zul Azam; Dimas Langga Chandra Galuh; M. Afif Shulhan (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2024)
Year by year, there has been a sharp increase in the development of roads, buildings, and other infrastructures focused on communities in various parts of the country. This growth has driven the construction sector to work more efficiently and integrated, especially with the advancement of technology and communication. Building Information Modeling (BIM), which allows for more efficient and integrated design and construction processes, is one of the new options. However, effective time and cost planning remain major challenges. Therefore, careful planning is essential to ensure the success of construction projects. BIM enables building modeling in three dimensions, which helps in better project visualization. One of the most commonly used BIM programs is Autodesk Revit, which combines various disciplines such as architecture, structure, and MEP (Mechanical, Electrical, Plumbing).